2017
DOI: 10.1002/jmrs.208
|View full text |Cite
|
Sign up to set email alerts
|

Reduced patient anxiety as a result of radiation therapist-led psychosocial support: a systematic review

Abstract: Up to 49% of patients attending radiation therapy appointments may experience anxiety and distress. Anxiety is heightened during the first few visits to radiation oncology. Radiation therapists (RT) are the only health professionals in direct daily contact with patients during treatment, placing them in a unique position to explore patients’ psychosocial needs. This review aims to synthesise literature regarding the effect of RT‐led psychosocial support on patient anxiety. In May 2015, we searched the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 25 publications
2
64
0
Order By: Relevance
“…The ‘RTs and Psychosocial Support Survey’ instrument was developed to address gaps in the literature regarding provision of psychosocial support in the radiation oncology setting (Table ). Existing items were embedded and literature‐guided survey development to ensure data could be compared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ‘RTs and Psychosocial Support Survey’ instrument was developed to address gaps in the literature regarding provision of psychosocial support in the radiation oncology setting (Table ). Existing items were embedded and literature‐guided survey development to ensure data could be compared.…”
Section: Discussionmentioning
confidence: 99%
“…The review indicated RTs do provide daily supportive care that can reduce anxiety, fear and loneliness. To achieve this, RTs build rapport with patients and provide emotional comfort, information and education . RT use of screening and needs assessment tools was shown to be feasible and resulted in increased communication and knowledge of patients’ psychosocial concerns .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis by Elsner, Naehrig, Halkett, and Dhillon (2017) reviewed the effectiveness of psychosocial support provided by radiation therapists on patient anxiety levels in 12 studies comprising 1,363 patients. A recent meta-analysis by Elsner, Naehrig, Halkett, and Dhillon (2017) reviewed the effectiveness of psychosocial support provided by radiation therapists on patient anxiety levels in 12 studies comprising 1,363 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education is known to be a vital element of providing high quality care in radiation therapy (RT) . Effective patient education has positive impacts on patient consent, collaboration during treatment, patients’ empowerment and psychosocial well‐being . However, ‘radiation’ and the processes of RT are known to be difficult concepts for patients to understand, due to the complex nature of radiation as both a therapy and a danger, and a wide array of learner factors due to the diversity of cancer patient presentations, health literacy and competency in the local language …”
Section: Introductionmentioning
confidence: 99%